2018
DOI: 10.1021/acsaem.8b01536
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Evaluation of Coreduced Fe–Pt Metal Acetylacetonates as PEM Fuel Cell Cathode Catalyst

Abstract: Platinum−iron nanoparticles were produced by solvothermal coreduction of organic Fe and Pt precursor compounds and supported on conventional Vulcan XC 72. Evaluation of oxygen reduction performance reveals a highly active surface with up to 5 times the specific activity of commercial Pt−Vulcan measured in O 2 -saturated 0.1 M HClO 4 . A particle size of 5.5 nm for the best performing sample, produced from an initial metal ratio of 1:1, provided 28% higher mass activity than the commercial reference. Membrane e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…In solvothermal processes, this phenomenon is rationalized by initial formation of Fe-rich seeds promoting gradual Pt precipitation and deposition. 5,35 Whether this explanation also satisfies our current synthesis conditions of rapid coreduction in the dry phase is unclear. After annealing (FePt(1:1)/C), the particle size shows a relatively small increase in size from ∼2.4 to ∼2.9 nm in conjunction with the increase in order parameter (see Supporting Information Figure S5), manifesting a remarkable resilience toward crystallite growth, which is commonly caused by either Ostwald ripening or support-detachment followed by migration and coalescence.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In solvothermal processes, this phenomenon is rationalized by initial formation of Fe-rich seeds promoting gradual Pt precipitation and deposition. 5,35 Whether this explanation also satisfies our current synthesis conditions of rapid coreduction in the dry phase is unclear. After annealing (FePt(1:1)/C), the particle size shows a relatively small increase in size from ∼2.4 to ∼2.9 nm in conjunction with the increase in order parameter (see Supporting Information Figure S5), manifesting a remarkable resilience toward crystallite growth, which is commonly caused by either Ostwald ripening or support-detachment followed by migration and coalescence.…”
Section: Resultsmentioning
confidence: 86%
“…A widening of the peaks corresponding to a decrease in particle sizes from ∼3 to ∼2 nm correlate to an increase in Fe/Pt ratio, indicating that the average NP size can be directly tuned by the fraction of the Fe precursor. In solvothermal processes, this phenomenon is rationalized by initial formation of Fe-rich seeds promoting gradual Pt precipitation and deposition. , Whether this explanation also satisfies our current synthesis conditions of rapid coreduction in the dry phase is unclear. After annealing (FePt(1:1)/C), the particle size shows a relatively small increase in size from ∼2.4 to ∼2.9 nm in conjunction with the increase in order parameter (see Supporting Information Figure S5), manifesting a remarkable resilience toward crystallite growth, which is commonly caused by either Ostwald ripening or support-detachment followed by migration and coalescence. , This observation is validated by experiments where we annealed the FePt(1:1)/C* in a conventional oven, resulting in an increase in a particle size of only ∼0.6 nm (particle size 3 nm) at 700 °C, likely owing to unusually firm adherence to the carbon support.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Since the electrocatalytic property of Pt-based nanomaterials can be tuned by manipulating the precursors, reaction conditions and preparation methods, one promising strategy to improve the electrochemical performance is alloying Pt with a second transition metal which holds advantages comparing with monometallic catalysts owing to the existence of synergistic effect between the two metals. A series of measures have been utilized in alloying Pt with Ni, 13,14 Cu, 15 Pd, 16 Fe, 17 and Pb. [18][19][20] Huang et al 19 successfully prepared platinum-lead concave nanocubes with excellent electrocatalytic performance towards methanol oxidation, which is contributed by the synergistic effect of Pt-Pb alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, theoretical and practical studies have shown that modication of the electron conguration within the Pt lattice can dramatically alter the surface adsorption of oxygen in a favorable direction such that the ORR results in a lowered overpotential. 7,8 This can be achieved by alloying Pt into binary or ternary congurations with 3d type transition metals such as Fe, [9][10][11] or Co, [15][16][17] which may enhance the ORR properties by mechanisms involving the creation of more close-packed surface facets of the face centered cubic (fcc) Pt lattice and/or inducing ligand effects. It is clear that this approach is highly convenient as it also dilutes the Pt within the nanoparticle core and may thus further contribute to an enhanced Pt mass activity.…”
Section: Introductionmentioning
confidence: 99%